Dysfunctional customer behavior influences on employees’ emotional labor: The moderating roles of customer orientation and perceived organizational support - Cheng, Pengfei; Jiang, Jingxuan; Xie, Sanbin; Liu, Zhuangzi (Frontiers in Psychology, 2022)
Despite increasing interest being given to dysfunctional customer behavior in multiple service sectors, it is unclear how and why the different type of dysfunctional customer behavior (verbal abuse, disproportionate demand, and illegitimate complaint) affects frontline employees’ emotional labor in service interactions. Drawing upon the conservation of resources theory (COR), we propose that dysfunctional customer behavior among different types may have a differential influence on emotional labor strategies (surface acting and deep acting) of frontline employees. Furthermore, perceived organizational support (POS) and customer orientation moderate these relationships. Using survey data from 436 frontline employees of call centers in China, the results indicated that verbal abuse and illegitimate complaint exert significant positive effects on surface acting. However, when customers are performing verbal abuse, disproportionate demand, or illegitimate complaint, frontline employees are more likely to report lower deep acting. It also found that POS and customer orientation moderate the relationships between dysfunctional customer behavior and employees' emotional labor: when the level of POS is high, the positive effects of customers’ verbal abuse and illegitimate complaint on employees' surface acting are weaker, and the negative effect of disproportionate demand on deep acting is also weaker; when the level of customer orientation is high, the positive effect of verbal abuse on employees' surface acting is weaker, and the negative effects of disproportionate demand and illegitimate complaint on deep acting are also weaker.